Discharge communication study: a realist evaluation of discharge communication experiences of patients, general practitioners and hospital practitioners, alongside a corresponding discharge letter sample. Issue 7 (21st July 2021) - Weetman, Katharine; Dale, Jeremy; Scott, Emma; Schnurr, Stephanie
Abstract : Objectives: To develop a programme theory for the intervention of patients receiving discharge letters. Design: We used a realist evaluation approach and captured multiple perspectives of hospital discharge to refine our previously developed programme theory. General practitioner (GP), patient and hospital clinician views of a single discharge event in which they were all involved were collected using semi-structured interviews and surveys. These were then triangulated to match the corresponding discharge letter. Data were qualitatively synthesised and compared in meta-matrices before interrogation with realist logic of analysis to develop the programme theory that maps out how patients receiving discharge letters works in specific contexts. Setting: 14 GP practices and four hospital trusts in West Midlands, UK. Participants: 10 complete matched cases (GP, patient and hospital practitioner), and a further 26 cases in which a letter was matched with two out of the three participants. Results: We identified seven context mechanism outcome configurations not found through literature searching. These related to the broad concepts of: patient preference for receiving letters, patient comprehension of letters, patient-directed letters, patient harm and clinician views on patients receiving letters. 'Patient choice' was important to the success (or not) of the intervention. Other important contexts for positive effects included: letters written in plain English, lay explanations for jargon, verbal information also provided, no new information in letter and patient choice acknowledged. Three key findings were: patient understanding is perhaps greater than clinicians perceive, clinician attitudes are a barrier to patients receiving letters and that, negative outcomes more commonly manifested when patients had not received letters, rather than when they had. Conclusions: We suggest how patients receiving discharge letters could be improved to enhance patient outcomes. Our programme theory has potential for use in different healthcare contexts and as a framework for policy development relating to patient discharge.